RANCANG BANGUN APLIKASI INVENTARIS RUANGAN MENGGUNAKAN LARAVEL 8 PADA PONDOK AR RAHMAN PALEMBANG - Arif Fadillah; Paray Theo Lonando (jurnal kesehatan terapan sains dan teknologi, 2023)
The development of information systems is so rapid today, the application of information systems engaged in the management of goods is one of the information systems that is widely used by organizations or companies. The implementation of the goods information system is essentially an effort to maintain orderly documents and orderly administration of goods management. Ordering goods documents is related to efforts to provide and collect data or documents that accompany the existence of goods, while orderly administration is more intended to develop procedures for managing goods from procurement, receipt, data change, to deletion of goods. For an agency the management of goods is very important. At Pondok Ar-Rahman Palembang, all activities (room inventory) are still carried out manually and in recording new items, old items and damaged items in each room are still not well controlled, it can be seen by the existence of data items that do not match the stock records. This study aims to design a web-based room inventory application at Pondok Ar-Rahman Palembang, which in each room can manage data on new items, old items and damaged items, so that a well-structured recapitulation of goods is carried out. The system development method is waterfall.